2011
DOI: 10.1007/s10014-011-0068-7
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic onset of cerebellar pilocytic astrocytoma in an adult: a case report and review of the literature implying a possible relation of degenerative vascular changes to the massive intratumoral hemorrhage

Abstract: Pilocytic astrocytoma (PA) is a low-grade astrocytic tumor arising predominantly during the first two decades of life. Hemorrhagic onset of PAs is uncommon, and the etiology of hemorrhage remains unclear. Here we report a case of hemorrhagic onset of cerebellar PA in a 29-year-old man who presented with a week-long history of headache and gait instability. Computed tomography and magnetic resonance imaging revealed a hemorrhagic tumor located in the right cerebellar hemisphere, and total resection was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…These vessels, despite being rich in collagen, have less of elastic fibers and less compliance. This added by high vascularity of tumor makes them prone to rupture [14]. The vessels in this tumor are thin walled and have reticular capillary structure.…”
Section: Discussionmentioning
confidence: 98%
“…These vessels, despite being rich in collagen, have less of elastic fibers and less compliance. This added by high vascularity of tumor makes them prone to rupture [14]. The vessels in this tumor are thin walled and have reticular capillary structure.…”
Section: Discussionmentioning
confidence: 98%
“…Progression of residual disease can be controlled by tumour re-excision and stereotactic radiosurgery [27, 28]. In the event of biopsy-proven pilocytic astrocytoma with anaplastic features, radiation therapy and/or chemotherapy will be required [12]. …”
Section: Infratentorial Manifestationsmentioning
confidence: 99%
“…Hwang, et al described a case of a 34-year-old man presenting with a hemorrhagic hypothalamic pilocytic astrocytoma [3]. Oka, et al reported on a 21-year-old man with a tectal pilocytic astrocytoma presenting with hemorrhage [9]. Lee, et al…”
Section: Discussionmentioning
confidence: 99%
“…Rupture within areas of this abnormal vasculature may be the etiology behind intratumoral hemorrhage of pilocytic astrocytomas. It has also been implied that some degree of degenerative vascular changes may be the underlying factor ultimately leading to hemorrhage, given the older age distribution of patients with hemorrhagic pilocytic astrocytomas [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation